Phytocompounds, Heavy Metal and Mineral Contents in honey Samples from Selected Markets in the Kumasi Metropolis - Nkansah, Marian Asantewah; Opoku, Francis; Shamsu–Deen, Mariam (Ital Publication, 2018)
The present study sought to determine the content of calcium (Ca), magnesium (Mg), lead (Pb), iron (Fe), zinc (Zn) and eight phytocompounds in honey collected from twenty–three markets in the Kumasi Metropolis of Ghana. The mineral and heavy metal contents were analysed using the Atomic Absorption Spectrometry (novAA® 400P) and phytoconstituents by standard qualitative procedures. This study revealed that Mg and Ca concentrations ranged from 3.61–15.93 mg/kg and not detected–3.24 mg/kg, respectively. The concentrations of Ca and Mg were within the Recommended Dietary Allowance and Nutrient Reference Value respectively; an indication that the honey can be used as food source rich in Mg and Ca. The levels of Fe, Zn and Pb were lower than the limit of detection, indicating their safety from metal contaminants. A considerable number of phytoconstituents were detected. In general, the results obtained indicate that the honey samples collected from the Kumasi metropolis are of good quality.